Comparative study of active infrared thermography, ultrasonic laser vibrometry and laser ultrasonics in application to the inspection of graphite/epoxy composite parts; Quantitative InfraRed Thermography Journal; Vol. XX - Vavilov V. P. Vladimir Platonovich; Karabutov A. A.; Chulkov A. O. Arseniy Olegovich; Derusova D. A. Dariya Aleksandrovna; Moskovchenko A. I. Aleksey Igorevich; Cherepetskaya E. B.; Mironova E. A. (2019, 2019)
Title screen